Asiaticoside alleviates ferroptosis in myelodysplastic syndrome by activating SMAD7 - WANG Liye; CHANG Qing; DONG Tengteng (陆军军医大学学报)
Objective‍　‍To investigate the relationship of aberrant SMAD family member 7 (SMAD7) signaling pathway and ferroptosis in myelodysplastic syndromes (MDS) and evaluate the effect of asiaticoside (AC)-modulating SMAD7 up-regulation to suppress ferroptosis in MDS cell lines. Methods‍　‍Publicly available MDS-related datasets from the Gene Expression Omnibus (GEO) database were analyzed to identify differentially expressed genes (DEGs) between MDS patients and healthy controls. These DEGs were cross-referenced with ferroptosis-associated genes from the Ferroptosis Database (FerrDb) to identify potential ferroptosis-related targets in MDS. Bone marrow mononuclear cells (BMMNCs) were isolated from 18 MDS patients freshly diagnosed in the First Medical Center of Chinese PLA General Hospitaland and from 16 healthy donors during October 2022 and November 2024. RT-qPCR was employed to detect the expression of SMAD7 and ferroptosis-related genes. Immunomagnetic bead sorting was applied to purify CD33+ cells, and then qPCR and Western blotting were utilized to measure the expression of SMAD7 and ferroptosis-related biomarkers at mRNA and protein levels. Human normal bone marrow cells (HS-5) and MDS cell lines (MUTZ-1, SKM-1) were treated with gradient concentrations of AC (SMAD7 activator) and ferrostatin-1 (Fer-1, ferroptosis inhibitor), and SMAD7 overexpression plasmids were transfected into MDS cells. qPCR and Western blotting were utilized to measure the expression of SMAD7 and ferroptosis-related biomarkers at mRNA and protein levels, and the contents of glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD), and reactive oxygen species (ROS) were detected. Flow cytometry of CD11b+ was performed to measure cellular differentiation. Results‍　①Bioinformatics analysis revealed significant down-regulation of SMAD7 in MDS patients, correlating with ferroptosis activation. Compared to the healthy controls, MDS patients exhibited decreased SMAD7 expression (P<0. 05), reduced levels of negative regulators of ferroptosis, glutathione peroxidase 4 (GPX4) and ferritin heavy chain (FTH1) (P<0.05), and elevated expression of its positive regulator transferrin receptor protein 1 (TFRC) (P<0.05). Consistent with this, when compared with the normal human bone marrow stromal cell line HS-5, the MDS cell lines MUTZ-1 and SKM-1 exhibited declined expression of SMAD7, GPX4, and FTH1, alongside elevated expression of TFRC (P<0.05). ② Treatment with gradient concentrations of the ferroptosis inhibitors ferrostatin-1 (Fer-1), the expression levels of GPX4 and FTH1 in MDS cell lines were significantly upregulated in a concentration-dependent manner (P<0.05), while TFRC was markedly downregulated (P<0.05). Additionally, GSH content and SOD activity were enhanced, whereas ROS levels and MDA content were significantly reduced (P<0.05). These results suggest that Fer-1 effectively suppresses ferroptosis in MDS cells. ③SMAD7 overexpression led to up-regulation of GPX4 and FTH1 ih MDS cell lines, while downregulation of TFRC, improved anti-oxidative ability and reduced ferroptosis, with enhanced CD11b+ expression and myeloid differentiation. ④ Following AC treatment, the expression levels of GPX4 and FTH1 in MDS cell lines were significantly upregulated in a concentration-dependent manner (P<0.05), whereas the downregulation of TFRC did not reach statistical significance. Additionally, AC treatment effectively enhanced the antioxidant capacity of the cells, increased the proportion of CD11b+ cells (P<0.05), and facilitated cellular differentiation. Conclusion‍　‍AC activates SMAD7 in MDS cell lines, up-regulating GPX4 and FTH1 while suppressing TFRC expression. This mechanism alleviates oxidative damage and lipid peroxidation, thereby inhibiting ferroptosis in MDS cells. Concurrently, SMAD7 activation promotes cellular differentiation.